Analysis of Psychological Growth of the Main Character in Chenlun by Yu Dafu - Lin, Xuc (Bina Nusantara University, 2008)
Article discusses the psychological aspect of the main character in the novel â€œChen Lunâ€. The feelings of inferiority and loneliness are his initial mental states. The latter is caused by two factors: the social and personality factors while the former is caused by the political condition in China at that time and the fact that the Japanese underestimate the Chinese people. The writer uses Freudâ€™s theory on the structure of personality and conflict, anxiety, and the defense mechanism to analyze the process of the psychological development of the main character. In the end of the story, the main character commits suicide since â€œheâ€ cannot only solve the problem of his loneliness and inferiority but also he feels guilty of his wrongdoing which crushes his-ideal-self. The guilty feeling haunts him in such a way that he even denies himself.